AGROWISATA HORTIKULTURA DENGAN PENDEKATAN KEARIFAN LOKAL DI TAWANGMANGU KABUPATEN KARANGANYAR - Angga Catur Romadhon; Widi Suroto; Tri Yuni Iswati (ARSITEKTURA, 2015)
Tawangmangu horticulture agrotourism is more specific agro present for agro tourism which includes fruits, vegetables, ornamental plants, and medicinal plants that have been cultivated and developed in the Tawangmangu. Agro horticulture design by many potential and prospects for development of agro tourism in Tawangmangu, and the number of outstanding issues which states that the existence of an agro tourism will damage and affect the balance of nature that result in natural disasters, such as flooding, erosion (landslides), and global warming. This happens due to the lack of principles of local wisdom that underlie the surrounding communities in the preservation of the environment are becoming increasingly eroded and disappeared. In the planning concept and its design, Agro horticulture uses the concept of local wisdom approach as the basis of planning and design which emphasizes environmental conservation and cropping patterns communities around the site right as part of the concept of local knowledge on which the architectural approach of the Agro Horticulture Tawangmangu. The problem is how to plan and design Agro horticulture educational and recreational as well as local wisdom characterized agro tourism. The method used is the technique of collecting data and analyzing them through the principles of local knowledge as an architectural approach. With the Agro horticulture of the local wisdom, is expected to produce an Agro Horticulture as a recreational vessel agro tourism and educational that can accommodate various types of tourist activities. Keywords: Agro Horticulture, Local Wisdom, Environmental Conservation, recreational, educative.